Start-off MHD electrokinetic Couette flow in an annulus: a Riemann-sum approximation approach - Oni, Michael O.; Jha, Basant K.; Abba, Junaid M.; Mundi, Baba I.; Adebayo, Olaife H. (Zielona Góra: Uniwersytet Zielonogórski)
The time dependent Couette flow (CF) of a conducting fluid formed between two concentric tubes with variable electric potential and accelerated motion of the outer cylinder is investigated. The governing electric field potential as well as the momentum equivalences are gotten from Poisson-Boltzmann and Navier Stokes Eqs respectively.
Keywords: electrokinetic; unsteady; Couette flow; annuli; MHD